2022
DOI: 10.1038/s41598-022-15536-5
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen use aggravates bacterial diversity and network complexity responses to temperature

Abstract: Rising temperature affects microbial composition and function in agriculture field, especially under nitrogen fertilization. In this study, we investigated the bacterial community of paddy soil incubated at controlled temperatures (5 °C, 15 °C, 25 °C, and 35 °C). Results showed that the response of bacterial communities to temperature was not uniform. Temperature elevation from 15 to 25 °C abruptly shifted the soil bacterial community, whereas elevation from 5 to 15 °C and from 25 to 35 °C had a marginal effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Another study also found that climatic factors could indirectly impact the composition of phyllosphere bacterial community by modulating bacterial interactions (Li et al, 2022c). It is almost certain that local changes in climate could have an impact on the ecosystem functioning of the phyllosphere microbiome given the narrow climatic endurance of its key microbial taxa (Xing et al, 2022). Besides, the links and nodes of the phyllosphere bacterial community networks from yellowhorn had positive and negative correlative relationships with the temperature and precipitation variables, respectively.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Another study also found that climatic factors could indirectly impact the composition of phyllosphere bacterial community by modulating bacterial interactions (Li et al, 2022c). It is almost certain that local changes in climate could have an impact on the ecosystem functioning of the phyllosphere microbiome given the narrow climatic endurance of its key microbial taxa (Xing et al, 2022). Besides, the links and nodes of the phyllosphere bacterial community networks from yellowhorn had positive and negative correlative relationships with the temperature and precipitation variables, respectively.…”
Section: Discussionmentioning
confidence: 95%
“…Work (Li et al, 2022c) also demonstrated that less precipitation could strengthen the interactions and cooperation between co-occurring microbial functional taxa, possibly due to greater bacterial separation and reduced competition between bacterial species under conditions of little precipitation (Treves et al, 2003). Previous studies also affirmed that appropriately higher temperatures could intensify both the network connectivity and complexity of microbial communities to improve the cooperation between member microbes to defend the impaired ecosystem functions (Yuan et al, 2021;Xing et al, 2022). Therefore, combining climatic factors and key microbial interactions could reinforce the regulation of phyllosphere bacterial community assembly on yellowhorn hosts.…”
Section: Discussionmentioning
confidence: 95%
“…All networks were visualized in Gephi software, and topological features of each network were also calculated in Gephi, including number of network nodes, number of edges, number of positive and negative correlations, average degree, network density, network diameter, network density, modularity, and average clustering coefficient. The details of network analyses referred to Xing et al (2022). Two functional prediction tools (PICRUST2 and FAPROTAX) were used to analyze the effects of OA on the functional potentials of microbial biofilms.…”
Section: Bioinformatics and Statistical Analysismentioning
confidence: 99%
“…Network density is defined as the fraction of edges present over all possible edges in the network. Both two parameters describe the connectivity of a network (Xing et al, 2022).…”
Section: Biofilm Community Structurementioning
confidence: 99%
See 1 more Smart Citation